Unpacking equity trends and gaps in Nepal’s progress on maternal health service utilization: Insights from the most recent Demographic and Health Surveys (2011, 2016 and 2022) - Resham B. Khatri; Rolina Dhital; Sabita Tuladhar; Nisha Joshi Bhatta; Yibeltal Assefa (PLoS ONE, 2025)
Background Improving maternal health is a global priority for overall socioeconomic development countries, especially in the low- and middle-income countries including Nepal. Recently, Nepal has made significant progress in enhancing access to maternal health services and in reducing maternal mortality ratio (MMR). Nonetheless, the MMR remains high (151 maternal deaths per 100,000 live births), with a slower rate of decline in recent years, particularly among disadvantaged groups. This study investigates trends and determinants of key maternal health services in Nepal. Methods We conducted further analysis of secondary data from the most recent three Nepal Demographic and Health Surveys (NDHS) conducted in 2011 (n = 1,057), 2016 (n = 964), and 2022 (n = 981) among women aged 15–49 who had at least one live birth prior to each survey. The outcome variables for the trend analysis included the uptake of at least four antenatal care (4ANC) visits, institutional deliveries, first postnatal care (PNC) within 48 hours of childbirth, and completion of all these three routine visits. Determinants of institutional delivery, delivery in private health facilities (HFs), cesarian section (CS) deliveries, and uptake of maternity incentive were investigated. Independent variables included socioeconomic characteristics of women and their marginalization status, geographic factors (e.g., province), health system factors (health service use). A multivariable logistic regression analysis was conducted using data from the NDHS 2022 to investigate the associated determinants of outcome variables considering p value <0.05. Results Results showed low completion rates (59%) of all three maternity care visits and significant discontinuity of care throughout the maternity continuum (82% 4ANC, and 73% PNC visits). From 2011 to 2022, there were increased institutional deliveries overall (47% to 81%) and CS within private HFs (30% to 51%), alongside a decreasing trend in the utilization of maternity incentives (87% to 78%). Women from Karnali province and those facing multiple forms of marginalization (women form lower wealth status and who belong to marginalized ethnicities (e.g., Dalits or Janajatis), and lack of education had lower odds of institutional delivery. Conversely, women who attended at least 4ANC visits had higher odds of institutional delivery. Higher odds of childbirth in private HFs were identified in the Koshi, Bagmati, Madhesh, and Lumbini provinces, particularly among women with fewer forms of marginalization. In contrast, women who worked as manual labor or those with higher birth orders had lower odds of childbirth in private HFs. Notably, higher odds of delivery by CS were observed among older women, women who were Maithili native speakers, and in provinces where higher delivery in HFs. Furthermore, the odds of uptake of maternity incentives were lower among women who had gave births in private HFs. Conclusions Marginalized women experience lower uptake of routine maternity care visits and higher discontinuation along the antenatal through to ponstantal period, creating significant equity gaps in Nepal. The increasing trend of deliveries in private HFs, particularly deliveries by elective CS without maternity incentives could lead to financial hardship while seeking routine maternal health care. Health systems should adopt targeted strategies addressing specific needs, considering intersecting marginalization factors. Key interventions include improving infrastructure, hiring and training local health workers, revising maternity incentives, regulating private HFs, and conducting quality audits, including increasing trends of CS deliveries.